A systematic review of assisted and third-party reproduction guidelines regarding management and care of donors - Elnaz Iranifard; Samira Ebrahimzadeh Zagami; Malihe Amirian; Hossein Ebrahimipour; Robab Latifnejad Roudsari (BMC, 2024)
Abstract Background Gamete and embryo donors face complex challenges affecting their health and quality of life. Healthcare providers need access to well-structured, evidence-based, and needs-based guidance to care for gamete and embryo donors. Therefore, this systematic review aimed to synthesize current assisted and third-party reproduction guidelines regarding management and care of donors. Methods The databases of ISI, PubMed, Scopus, and websites of organizations related to the assisted reproduction were searched using the keywords of "third party reproduction", "gamete donation", "embryo donation", "guidelines", "committee opinion", and "best practice", without time limit up to July 2023. All the clinical or ethical guidelines and best practice statements regarding management and care for gamete and embryo donors written in the English language were included in the study. Quality assessment was carried using AGREE II tool. Included documents were reviewed and extracted data were narratively synthesized. Results In this systematic review 14 related documents were reviewed of which eight were guidelines, three were practice codes and three were committee opinions. Five documents were developed in the United States, three in Canada, two in the United Kingdom, one in Australia, and one in Australia and New Zealand. Also, two guidelines developed by the European Society of Human Reproduction and Embryology were found. Management and care provided for donors were classified into four categories including screening, counseling, information provision, and ethical considerations. Conclusion While the current guidelines include some recommendations regarding the management and care of gamete/embryo donors in screening, counseling, information provision, and ethical considerations, nevertheless some shortcomings need to be addressed including donors' psychosocial needs, long-term effects of donation, donors' follow-up cares, and legal and human rights aspects of donation. Therefore, it is needed to conduct robust and well-designed research studies to fill the knowledge gap about gamete and embryo donors' needs, to inform current practices by developing evidence-based guidelines.